Characterization of tire and road wear particles from road runoff indicates highly dynamic particle properties. (15th October 2020) - Klöckner, Philipp; Seiwert, Bettina; Eisentraut, Paul; Braun, Ulrike; Reemtsma, Thorsten; Wagner, Stephan
Highlights: Strong correlations between Zn in density fraction <1.9 g/cm³, TED-GC/MS and organic compounds. Coarse TRWPs dominated road dust samples. Fine TRWPs dominated sediment of road runoff treatment system. Density of TRWPs was altered in aged sediments but was <1.9 g/cm³ in road dust samples. Abstract: Tire and road wear particles (TRWPs) are heteroagglomerates of tire rubber and other particles deposited on the road surface and one of the main contributors to non-exhaust emissions of automobile traffic. In this study, samples from road environments were analyzed for their TRWP contents and concentrations of eight organic tire constituents. TRWP concentrations were determined by quantifying Zn in the density fraction <1.9 g/cm³ and by thermal extraction desorption-gas chromatography-mass spectrometry (TED-GC/MS) and the concentrations ranged from 3.7 to 480 mg TRWP/g. Strong and statistically significant correlations with TRWPs were found for 2-hydroxybenzothiazole and 2-aminobenzothiazole, indicating that these substances may be suitable markers of TRWPs. The mass distribution of TRWPs in road dust suggests that the main mass fraction formed on roads consists of coarse particles (>100 µm). Data for a sedimentation basin indicate that the fine fraction (<50 µm) is preferentially transported by road runoff into receiving waters. The size distribution and density data of TRWP gathered by three different quantitation approaches also suggest that aging of TRWPs leads to changes in their particle density. An improved understanding of the dynamics of TRWP properties is essential to assess the distribution and dissipation of this contaminant of emerging concern in the environment. Graphical abstract: Image, graphical abstract